Student’s Perception of Learning Media Pencak Silat Based of Android - Iyakrus Iyakrus; Wahyu Indra Bayu; Arizky Ramadhan; Mutia Kartika (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This study aims to determine students' perceptions of the development of andorid-based martial arts material learning media in schools. This research is based on (1) Learning Media for android-based martial arts materials and (2) android-based martial arts learning materials. This research is a quantitative descriptive study. The subject of the study consisted of 30 students. The results of this study show that 1) Learning Media for android-based martial arts materials obtained a score of 90% with excellent categories and (2) Android-based martial arts Learning Materials obtained an 85% score with excellent categories. Based on this, it shows that the results of the Student's Perception Of Learning Media Pencak Silat Based Of Android are of positive value, this is the basis that it is necessary to develop martial arts learning media.